Peran W-O-M Memediasi Pengaruh Citra Toko Terhadap Minat Beli Konsumen di PD Manis Dempo Palembang - Meirisa, Faradila; Budianto, Yosep (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
This study aims to examine store image on consumer buying interest mediated by word of mouth promotions for PD Manis Dempo Palembang consumers. Data was collected using an online questionnaire and respondents were selected using a purposive sampling technique. Total respondents in this study were 190 consisting of 70 men and 120 women. The data is processed using the PLS Smart-3 structural equation model. As a result, store image has a positive and significant effect on purchase intention, store image has a positive and significant effect on word of mouth, word of mouth has an effect on purchase intention and store image has an effect on purchase intention which is mediated by word of mouth variables